Learning Barriers in Web Programming Subjects Among Vocational Software Engineering Students: A Qualitative Case Study - Akbar Wiguna; Rahmania Sri Untari; Fitria Nur Hasanah; Cindy Cahyaning Astuti; Arsyah Agas Awwaby (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2026)
This study examines the learning difficulties experienced by vocational high school (SMK) students in the Computer and Network Engineering (TKJ) program in learning web programming. A qualitative case study approach was employed, involving semi-structured interviews, observations, and documentation with 21 students from SMK Negeri 2 Buduran. Data were analyzed using thematic analysis supported by descriptive questionnaire results. The findings show that all students perceived web programming as challenging, with 71% rating it as very difficult and 29% as moderately difficult, while none considered it easy. In terms of learning enjoyment, 76% of students reported a neutral level of enjoyment, indicating limited intrinsic motivation. The analysis revealed several dominant learning barriers, including difficulties with programming syntax and logic, challenges in using development tools such as VSCode and terminal environments, limited access to clear learning resources, and insufficient instructional guidance. Emotional factors, such as frustration and stress caused by repeated errors, further hindered the learning process. Students also identified programming, networking (e.g., TCP/IP and server administration), and microcontroller-related subjects as the most difficult areas within the curriculum. These findings indicate that students’ learning difficulties in web programming are not only technical but also instructional and affective in nature. Therefore, this study emphasizes the need for more interactive, supportive, and student-centered learning strategies. The adoption of project-based learning, enhanced digital learning resources, and guided mentorship is recommended to improve students’ competencies, motivation, and confidence in web programming. The results provide valuable insights for educators, curriculum developers, and policymakers in strengthening vocational education to better meet industry demands.